DOI: 10.31274/rtd-180813-10329
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic parameters in two maize recurrent selection programs

Abstract: Recurrent selection is a cyclical breeding procedure that focuses on improving the mean performance of a population by increasing the frequency of favorable alleles, while maintaining adequate genetic variability for continued selection. Iowa Stiff Stalk Synthetic (BSSS) is a maize population that has undergone continuous recurrent selection for more than 50 years as the base population for two independent selection programs (intra-and inter-population). This study was designed to estimate the mean performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(51 reference statements)
0
1
0
Order By: Relevance
“…Their results suggest that the dominance variance should decrease with selection within the populations themselves, but the dominance variance should increase in the interpopulation cross. Holthaus (1994) reported that the estimates of dominance variance decreased within the BSSS population. The estimates suggest that the dominance variance should increase in the interpopulation cross, but no trend was detected in the estimates of dominance variance for grain yield (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Their results suggest that the dominance variance should decrease with selection within the populations themselves, but the dominance variance should increase in the interpopulation cross. Holthaus (1994) reported that the estimates of dominance variance decreased within the BSSS population. The estimates suggest that the dominance variance should increase in the interpopulation cross, but no trend was detected in the estimates of dominance variance for grain yield (Table 2).…”
Section: Discussionmentioning
confidence: 99%